Ecological IPM Farmer Field School for sustainable potato pest management in Batu’s millennial farmers - Luqman Qurata Aini; Bayu Aji Pamungkas; Abdul Latief Abadi; Arie Srihardyastutie; Novi Khila Firani; Mochamat Nurhadi; Afina Fitri Pratiwi; Salwa Resty Daffanti; Akhmad Rizal Oktafian; Valia Istifada; Chornelius Glori Yulio; Puguh Prastiyo Hutomo Nurhadi; Rizky Dwi Hamdani Nurhadi; Nuris Saadah; Muhammad Fariq Al Husni (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The Taruna Tani Abinaya Milenial Group in Sumber Brantas Village faces serious challenges in potato cultivation due to pest and disease attacks. Endemic diseases such as late blight (Phytophthora infestans) and potato cyst nematodes (Globodera sp.), along with infestations of leaf miner (Lyriomyza sp.), have reduced yields by up to 80–100 percent. This condition is further exacerbated by heavy reliance on synthetic pesticides, leading to high production costs, pest resistance, and soil quality degradation. To address these problems, an Ecological Integrated Pest Management Farmer Field School (IPM-FS) was implemented with the aim of improving agroecosystem health while reducing chemical pesticide use. The IPM-FS was carried out through a participatory extension approach using andragogy and discovery learning methods. Activities included the development of site-specific potato cultivation SOPs, the establishment of study plots, and training on the production of organic fertilizers, botanical pesticides, and local microorganisms. Evaluation results showed that 50 percent of participants were very satisfied with the learning materials, 44 percent were satisfied with the methods, and 94 percent supported the program’s continuation. This program proved effective in enhancing farmers’ knowledge and skills in environmentally friendly farming practices. The preparation of ecological IPM-based SOPs serves as a guideline for implementing Good Agricultural Practices (GAP).